Source estimate and tsunami forecast from far‐field deep‐ocean tsunami waveforms—The 27 February 2010 Mw 8.8 Maule earthquake. Issue 2 (23rd January 2016) - Yoshimoto, Masahiro; Watada, Shingo; Fujii, Yushiro; Satake, Kenji
Abstract: We inverted the 2010 Maule earthquake tsunami waveforms recorded at DART (Deep‐ocean Assessment and Reporting Tsunamis) stations in the Pacific Ocean by taking into account the effects of the seawater compressibility, elasticity of the solid Earth, and gravitational potential change. These effects slow down the tsunami speed and consequently move the slip offshore or updip direction, consistent with the slip distribution obtained by a joint inversion of DART, tide gauge, GPS, and coastal geodetic data. Separate inversions of only near‐field DART data and only far‐field DART data produce similar slip distributions. The former demonstrates that accurate tsunami arrival times and waveforms of trans‐Pacific tsunamis can be forecast in real time. The latter indicates that if the tsunami source area is as large as the 2010 Maule earthquake, the tsunami source can be accurately estimated from the far‐field deep‐ocean tsunami records without near‐field data. Key Points: DART data inversion with new Green's functions produces slip distribution similar to joint inversion Inversion of near‐field DART data can be used for real‐time tsunami forecast at far field Tsunami source can be accurately estimated from far‐field DART data only